A Direct Quantitative Raman Method for the Measurement of Dissolved Bisulfate in Acid-Sulfate Fluids. Issue 8 (August 2018) - Xi, Shichuan; Zhang, Xin; Luan, Zhendong; Du, Zengfeng; Li, Lianfu; Wang, Bing; Cao, Lei; Lian, Chao; Yan, Jun
Raman spectroscopy has been applied to the quantitative analysis of the concentration of bisulfate in acid-sulfate fluids at different temperatures. The quantitative analysis method is based on the peak area ratios ofHSO 4 - (ν1 ) and H2 O (ν2 ), where PA (HSO 4 - /H2 O) = [HSO 4 - ] × (0.0066 × T + 1.3070) at a temperature range of 0–100 ℃. We found that the molal scattering coefficient of bisulfate increases slightly at the elevated temperature may be due to the changes of fraction of water molecules that are hydrogen-bonded. The method can also be applied to analyze physicochemical parameters of other acid fluids, such as hydrogen phosphate, bicarbonate, etc., and especially to the in situ detection of deep sea acid-sulfate hydrothermal fluids in the future.